Compassionate Removal of Heated High-Flow Nasal Cannula for End of Life: Case Series and Protocol Development. Issue 4 (August 2021) - Brackett, Hareklia; Forman, Andrea; Foster, Laura A.; Fischer, Stacy M.
Abstract : Patients often receive burdensome care at the end of life in the form of interventions that may need to be removed. Heated high-flow oxygen delivered through a nasal cannula (HHFNC) is one such intervention that can be delivered in the hospital yet is rarely available outside of this setting. During the COVID-19 (coronavirus disease 2019) pandemic, health care systems continue to face the possibility of rationing critical life-sustaining equipment that may include HHFNC. We present a clinical protocol designed for weaning HHFNC to allow a natural death and ensuring adequate symptom management throughout the process. This was a retrospective chart review of 8 patients seen by an inpatient palliative care service of an academic tertiary referral hospital who underwent terminal weaning of HHFNC using a structured protocol to manage dyspnea. Eight patients with diverse medical diagnoses, including COVID-19 pneumonia, underwent terminal weaning of HHFNC according to the clinical protocol with 4 down-titrations of approximately 25% for both fraction of inspired oxygen and liter flow with preemptive boluses of opioid and benzodiazepine. Clinical documentation supported good symptom control throughout the weaning process. This case series provides preliminary evidence that the clinical protocol proposed has the ability to ensure comfort through terminal weaning of HHFNC.